Growth, stool consistency and bone mineral content in healthy term infants fed sn-2-palmitate-enriched starter infant formula: A randomized, double-blind, multicentre clinical trial. Issue 3 (June 2019) - Béghin, Laurent; Marchandise, Xavier; Lien, Eric; Bricout, Myriam; Bernet, Jean-Paul; Lienhardt, Jean-François; Jeannerot, Françoise; Menet, Vincent; Requillart, Jean-Christophe; Marx, Jacques; De Groot, Nanda; Jaeger, Jonathan; et al.
Summary: Background: Palmitate in breast milk is predominantly located in the triacylglycerol sn -2 position, while infant formulae contain palmitate predominantly in the sn -1 and sn -3 positions. During digestion, palmitate in the sn -1 and sn -3 positions is hydrolyzed to free palmitic acid that can subsequently complex with calcium to form insoluble soaps; this may partially explain why formula-fed infants have harder stools than breast-fed infants. Methods: This large (n = 488) randomized, double-blind, multicentre trial investigated whether increasing the sn -2 palmitate content of infant formula improves stool consistency and bone mineral content (measured by dual-energy x-ray absorptiometry), without affecting growth or health. From ∼1 week to 4 months of age, infants were exclusively fed one of three formulae: i ) control formula (CF; 16% of total palmitate at sn -2; n = 162), ( ii ) experimental formula 1 (EF1; 43% of total palmitate at sn -2; n = 166) or ( iii ) experimental formula 2 (EF2; 51% of total palmitate at sn -2; n = 160). Results: Intention-to-treat analysis showed softer stools in both EF groups ( vs. CF) at ages 2 weeks and 1 and 2 months (p ≤ 0.01), but not 3 and 4 months. At 4 months, all groups had similar growth outcomes while bone mineral content was significantly higher in EF1 (p = 0.0012) and EF2 (p = 0.0002) compared with CF. Comparison of reported adverse events up to 12 months revealed no differences among groups. All 3 infant formulae exhibited equally good digestive tolerance. Conclusions: Formulae enriched in sn -2 palmitate fed in early infancy are safe, improve stool consistency (from 2 weeks to 2 months) and increase bone mineral content (at 4 months).